2022
DOI: 10.12669/pjms.38.7.5377
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of distribution and drug resistance of pathogenic bacteria in blood culture of Dalian Municipal Central Hospital from 2015 to 2019

Abstract: Objectives: To analyze the distribution of common pathogenic bacteria and pattern of drug resistance in the blood culture of inpatients. Methods: This was a descriptive study. Blood culture data of inpatients of Dalian Municipal Central Hospital from January 2017 to December 2020 were collected from microbiology laboratory for retrospective analysis. Results: A total of 24,786 specimens were submitted for examination from inpatients from 2015 to 2019, and 2131 strains of clinically non-repetitive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…These studies consistently identified Gram-positive bacteria as the prevailing culprits responsible for BSI. 5 , 23 , 24 According to the findings of this investigation, E. coli (44.8%) emerged as the predominant causative agent, followed closely by K. pneumoniae (17.5%, 639/3660) and S. aureus (9.2%). This discovery aligns with previous reports from diverse countries and regions.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…These studies consistently identified Gram-positive bacteria as the prevailing culprits responsible for BSI. 5 , 23 , 24 According to the findings of this investigation, E. coli (44.8%) emerged as the predominant causative agent, followed closely by K. pneumoniae (17.5%, 639/3660) and S. aureus (9.2%). This discovery aligns with previous reports from diverse countries and regions.…”
Section: Discussionmentioning
confidence: 76%
“… 3 The pathogenic spectrum and pattern of antibiotic resistance of BSI vary among affected regions due to distinct epidemiological and geographic factors. 4 , 5 Monitoring data from Dalian, China, from 2015 to 2019 showed that Gram-positive cocci were the most prevalent BSI pathogens in blood cultures. 6 In contrast, antibiotic resistance surveillance data from Korea and Europe revealed that E. coli and S. aureus were the most common pathogens of, BSI.…”
Section: Introductionmentioning
confidence: 99%
“…The 4th edition of the "National Guide to Clinical Laboratory Procedures" was followed strictly during all operations, and the M100-S31 document of the Clinical and Laboratory Standards Institute (CLSI) was used to judge the results. 9 2.5.3 Quality control Zhengzhou Biocell Biotechnology Liability Company provided the VITEK 2 Compact automatic microbial analysis system, the BacT/ALERT 3D 480 automatic blood culture instrument ((bioMérieux), blood culture bottles, blood agar plates, and MacConkey agar plates. Before the tests, quality control strains (Escherichia coli (ATCC ® 25922), Pseudomonas aeruginosa (ATCC ® 27853), and S. aureus (ATCC ® 25923), provided by the Clinical Laboratory Centre of the Ministry of Health of China, were used to test the sterility and performance of the culture media and the quality of the antimicrobial disks.…”
Section: Culture and Microorganism Identi Cationmentioning
confidence: 99%